Modeling, design, and optimization of net-zero energy buildings. - (:unkn) unknown (Ernst & Sohn, 2015)
Bei Neubauten wird von den meisten Industrieländern langfristig das Ziel von Netto-Nullenergiegebäuden verfolgt. Das Buch hilft Planern bei der optimalen Nutzung von Simulationstools für die Planung von Netto-Nullenergiegebäuden und es werden sowohl moderne Modellierungstechniken als auch eingehende Einzelfallstudien vorgestellt.

After presenting the fundamental concepts, design strategies, and technologies required to achieve net-zero energy in buildings, the book discusses different design processes and tools to support the design of net-zero energy buildings (NZEBs). A substantial chapter reports on four diverse NZEBs that have been operating for at least two years. These case studies are extremely high quality because they all have high resolution measured data and the authors were intimately involved in all of them from conception to operating. By comparing the projections made using the respective design tools with the actual performance data, successful (and unsuccessful) design techniques and processes, design and simulation tools, and technologies are identified.
Keywords: Bebauung; Gebäude; Energieverbrauch; Optimierung; Design; Entwurf; Bautechnik; Neubau; Einfamilienhaus; Baukonstruktion; Bautypologie; Nullenergiehaus